2000
DOI: 10.1177/014556130007900708
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Comparisons of Craniofacial and Upper Airway Structures in Young Children with Obstructive Sleep Apnea Syndrome

Abstract: We studied 15 children ofpreschool age who had obst ructive sleep apnea syndrom e to evaluate thei r dentof acial morph ology in relation to the pharyngeal airway spac e. We fo und that (1) sleep apnea was often associated with mandibular retrognathia , (2) the lower incisors tended to exhibit a retroclin e, (3) there were no signific ant differences in angular and linear measurements in the cranial base between pat ients with sleep apnea and a control group of30 nonapn eic children, and (4) the apn eic childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 14 publications
1
37
2
3
Order By: Relevance
“…To evaluate the upper airway in children with OSAS, several radiologic techniques are available, including lateral neck radiographs, cephalometrics, fluoroscopy, computerized tomography, and magnetic resonance imaging (MRI) (29)(30)(31). The above modalities have all demonstrated that the upper airway of children with OSAS is smaller on average than compared with that of normal children.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…To evaluate the upper airway in children with OSAS, several radiologic techniques are available, including lateral neck radiographs, cephalometrics, fluoroscopy, computerized tomography, and magnetic resonance imaging (MRI) (29)(30)(31). The above modalities have all demonstrated that the upper airway of children with OSAS is smaller on average than compared with that of normal children.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Measurements of the pharyngeal airway space (18,(20)(21)(22) and the hyoid bone position (23,24): na-s-ba: the angle between na-s and s-ba .…”
Section: Cephalometric Analysismentioning
confidence: 99%
“…The soft-tissue morphology of the upper airway that may related to pediatric SDB includes narrowed pharyngeal airways, and larger adenoids, tonsils and soft palates [8-10]; the related hard-tissue morphology includes an increased intermaxillary angle, a retrognathic mandible [11,12], an increased mandibular angle, a longer lower anterior facial height [13,14], narrow dental arches and deep palatal height [15,16], and an inferiorly positioned hyoid bone [17,18]. …”
Section: Introductionmentioning
confidence: 99%